ANALISIS PERAN MEDIA PEMBELAJARAN TERHADAP MINAT BELAJAR SISWA SEKOLAH DASAR - Nurirpansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning interest is one of the important factors that determine the success of the learning process for elementary school students. However, in practice, learning is still often carried out conventionally with limited use of media, resulting in low interest and participation of students in learning. Learning media is seen as a means of creating learning that is more interesting, interactive, and meaningful for students. This study aims to analyze the role of learning media on elementary school students' interest in learning based on relevant research results. The research method used is a qualitative descriptive approach with a literature study method. Data were obtained from various sources, including national and international scientific journal articles and reference books discussing learning media and the learning interest of elementary school students over the past five to seven years. Data collection was carried out through documentation, while data analysis used content analysis. The results of the study show that interactive learning media, digital learning media, and visual media have a positive effect on increasing the learning interest of elementary school students. Interactive and digital media proved to be more effective than conventional learning media because they were able to increase students' active involvement, attention, and enthusiasm in the learning process. However, conventional media still plays a supporting role in strengthening students' basic understanding. Thus, the creative and integrated use of learning media can be an effective strategy in increasing the learning interest of elementary school students.